Prefrontal activation predicts social functioning improvement after initial treatment in late-onset depression - Pu, Shenghong; Nakagome, Kazuyuki; Yamada, Takeshi; Yokoyama, Katsutoshi; Matsumura, Hiroshi; Nagata, Izumi; Kaneko, Koichi (Journal of Psychiatric Research, 2015)
The activation of oxygenated hemoglobin (oxy-Hb) has been shown to be lacking in the prefrontal cortex (PFC) of patients with late-onset depression (LOD), in verbal fluency task (VFT)-related near-infrared spectroscopy (NIRS). In our previous studies, we have emphasized the connection between the lack of activation in the frontopolar cortex and social functioning disorder in patients with LOD. In this study, we investigated whether the responsiveness to medical treatment of untreated patients with LOD, particularly social functioning improvements, could be predicted by NIRS findings at the initial examination. The subjects were 29 patients with LOD who were diagnosed with major depression at 65 years or older at the initial examination (mean age ± standard deviation, 72.4 ± 5.71 years). We measured the changes in hemoglobin concentration in the prefrontal and temporal cortex regions during a VFT by using 52-channel NIRS. In addition, depression status and social functioning were evaluated with the Hamilton Depression Rating Scale and the Social Adaptation Self-evaluation Scale, respectively, at the initial examination and 8 weeks after the treatment. A negative correlation was found between the NIRS activation in the right ventrolateral PFC region before treatment and the improvement in social functioning. These results suggested that the social functioning improvements were greater in LOD with initially lower NIRS activation in the right ventrolateral PFC region. NIRS is a simple technique that can be used before treatment to evaluate the social functioning levels of patients with LOD, and predict social functioning improvement after treatment. •We studied brain cortex activity and social functioning improvements in late onset depression (LOD).•Prefrontal cortex (PFC) activity was measured using near-infrared spectroscopy (NIRS).•Right ventrolateral PFC activity predict social functioning improvement after treatment in LOD.•NIRS findings might be a useful indicator for social functioning improvements in LOD.